2015
DOI: 10.1111/clr.12719
|View full text |Cite
|
Sign up to set email alerts
|

Peri‐implant tissues morphometry at SLActive surfaces. An experimental study in the dog

Abstract: The tissue changes observed during the healing were similar to those from historic controls studying healing in a chamber adjacent to implants. Hence, the characteristics of the implant surfaces may not be reflected in the tissue composition adjacent to the implant but rather affect the adhesion of tissue onto the implant surfaces.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
5
0

Year Published

2016
2016
2020
2020

Publication Types

Select...
6

Relationship

3
3

Authors

Journals

citations
Cited by 8 publications
(7 citation statements)
references
References 19 publications
2
5
0
Order By: Relevance
“…; Favero et al. ). The healing in the internal zone appeared to follow a slightly different pattern compared to the other two zones.…”
Section: Discussionmentioning
confidence: 96%
“…; Favero et al. ). The healing in the internal zone appeared to follow a slightly different pattern compared to the other two zones.…”
Section: Discussionmentioning
confidence: 96%
“…In another experiment in dogs (Favero et al. ), the percentages of tissue components were evaluated in paraffin sections around a SLActive ® surface after different periods of healing. Provisional matrix reached percentages of 33% and 37% already after 4 and 7 days of healing, respectively.…”
Section: Discussionmentioning
confidence: 99%
“…In another experiment in dogs (Favero et al. ), the healing at a SLActive ® surface was morphometrically analyzed after various periods of healing. Provisional matrix was found at a percentage of 33% already after 4 days and, after 7 days, reached 37%.…”
Section: Discussionmentioning
confidence: 99%
“…; Favero et al. ). It has been shown that the healing at implant surface started with the formation of a coagulum, followed by a granulation tissue and the development of a provisional matrix.…”
mentioning
confidence: 96%